The Central Bank Transparency Code. (Policy Papers; Policy Paper ;, 2020)
The paper reports to the Executive Board on its decision of April 29, 2019, to prepare an IMF Central Bank Transparency Code (CBT), which is linked to the 2017 Review of the Standards and Codes Initiative (RSCI), for a revision and update of the 1999 Monetary and Financial Policies Transparency Code (MFPT). Directors asked that the CBT should remove the overlap on financial policies covered by other international standards, expand the transparency standards to broader set of activities undertaken by many central banks since the 2008 financial crisis, and reorient the transparency standards to facilitate risk-based assessments to support policy effectiveness and address macroeconomic risks.